Diagnostic Evaluation and Management of Chronic Thromboembolic Pulmonary Hypertension: A Clinical Practice Guideline. Issue 6 (2010) - Mehta, Sanjay; Helmersen, Doug; Provencher, Steeve; Hirani, Naushad; Rubens, Fraser D; De Perrot, Marc; Blostein, Mark; Boutet, Kim; Chandy, George; Dennie, Carole; Granton, John; Hernandez, Paul; et al.
Abstract : BACKGROUND: Pulmonary embolism is a common condition. Some patients subsequently develop chronic thromboembolic pulmonary hypertension (CTEPH). Many care gaps exist in the diagnosis and management of CTEPH patients including lack of awareness, incomplete diagnostic assessment, and inconsistent use of surgical and medical therapies. METHODS: A representative interdisciplinary panel of medical experts undertook a formal clinical practice guideline development process. A total of 20 key clinical issues were defined according to the patient population, intervention, comparator, outcome (PICO) approach. The panel performed an evidence-based, systematic, literature review, assessed and graded the relevant evidence, and made 26 recommendations. RESULTS: Asymptomatic patients postpulmonary embolism should not be screened for CTEPH. In patients with pulmonary hypertension, the possibility of CTEPH should be routinely evaluated with initial ventilation/ perfusion lung scanning, not computed tomography angiography. Pulmonary endarterectomy surgery is the treatment of choice in patients with surgically accessible CTEPH, and may also be effective in CTEPH patients with disease in more 'distal' pulmonary arteries. The anatomical extent of CTEPH for surgical pulmonary endarterectomy is best assessed by contrast pulmonary angiography, although positive computed tomography angiography may be acceptable. Novel medications indicated for the treatment of pulmonary hypertension may be effective for selected CTEPH patients. CONCLUSIONS: The present guideline requires formal dissemination to relevant target user groups, the development of tools for implementation into routine clinical practice and formal evaluation of the impact of the guideline on the quality of care of CTEPH patients. Moreover, the guideline will be updated periodically to reflect new evidence or clinical approaches.